2022
DOI: 10.3389/fmed.2021.815628
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Adenomyosis Is Associated With Postoperative Recurrence of Ovarian Endometrioma

Abstract: Objective: To determine whether endometrioma recurrence is closely related to the presence of extrinsic adenomyosis, which was demonstrated by magnetic resonance imaging (MRI).Design: Observational crosssectional study involving patients with the recurrence of ovarian endometrioma (OMA). Correlations of endometrioma recurrence and adenomyosis subtypes shown by MRI were analyzed.Method: Between January 2018 and December 2020, a total of 233 patients with recurrence of OMA after ovarian cystectomy were administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…In our study, the presence of adenomyosis is another independent risk factor for the recurrence of endometrioma. Sun Man et al [ 21 ] found that extrinsic adenomyosis was significantly correlated with the early recurrence of endometrioma. Libo Zhu et al found that the recurrence rate of AM combined with EM at 6 years after operation was higher than that of AM alone group [ 22 ], indicating that EM and AM influenced each other.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the presence of adenomyosis is another independent risk factor for the recurrence of endometrioma. Sun Man et al [ 21 ] found that extrinsic adenomyosis was significantly correlated with the early recurrence of endometrioma. Libo Zhu et al found that the recurrence rate of AM combined with EM at 6 years after operation was higher than that of AM alone group [ 22 ], indicating that EM and AM influenced each other.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the distinctive imaging features and various MRI-based subtypes of adenomyosis [11,12], which can pose a diagnostic dilemma, must be recognized. Extrinsic adenomyosis was significantly correlated with early ovarian endometrioma recurrence in less than three years [19]. In co-existing endometriosis and adenomyosis cases, patients must be informed about its chronic nature, potentially affecting the long-term overall quality of life, including mental health, social activities, and partner relationships.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with extensive adenomyosis were not considered for surgery [13] (Figure 1). Uterus and adenomyotic lesions were treated as triaxial ellipsoids; their volumes were calculated using the following formula: volume = 0.523 × longitudinal diameter × anteroposterior diameter × transverse diameter [14].…”
Section: Diagnosis Of Adenomyosis and Calculation Of Uterus And Adeno...mentioning
confidence: 99%